2022
DOI: 10.1177/1354067x221147683
|View full text |Cite
|
Sign up to set email alerts
|

Reification of infant-directed speech? Exploring assumptions shaping infant-directed speech research

Abstract: The seemingly ubiquitous tendency of caregivers to speak to infants in special ways has captivated the interest of scholars across diverse disciplines for over a century. As a result, this phenomenon has been characterized in quite different ways. Here, we highlight the shift from early definitions of “baby-talk” which implied that the nature of speech directed towards infants would vary in different sociolinguistic contexts, to later terms such as “motherese” or “infant-directed speech” (IDS) which came to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 105 publications
(160 reference statements)
0
4
0
Order By: Relevance
“…The pivotal measure of mean length of utterance has only been compared in one study (Ko et al, 2020) which used two ADS registers for comparison, a less formal one directed at a family member and a more formal one directed at the experimenter. Interestingly, this study found that syntactic complexity was lower in CDS compared to informal but not to formal ADS, an intriguing finding suggesting that the familiarity confound plaguing many CDS-ADS comparisons (Weinstein & Baldwin, 2022) may, in fact, have led to an underestimation of differences between CDS and ADS, a suggestion that certainly needs further investigation. A few other studies have focussed on comparing overall utterance length (Kaye, 1980;Lee et al, 2008;Martin et al, 2016;Vigário et al, 2006) but often with the goal of explaining the origins of certain prosodic and phonological characteristics of CDS as a by-product of utterance-length differences.…”
Section: Gap 1: Comparisons Between Cds and Ads In Morphosyntactic Le...mentioning
confidence: 69%
“…The pivotal measure of mean length of utterance has only been compared in one study (Ko et al, 2020) which used two ADS registers for comparison, a less formal one directed at a family member and a more formal one directed at the experimenter. Interestingly, this study found that syntactic complexity was lower in CDS compared to informal but not to formal ADS, an intriguing finding suggesting that the familiarity confound plaguing many CDS-ADS comparisons (Weinstein & Baldwin, 2022) may, in fact, have led to an underestimation of differences between CDS and ADS, a suggestion that certainly needs further investigation. A few other studies have focussed on comparing overall utterance length (Kaye, 1980;Lee et al, 2008;Martin et al, 2016;Vigário et al, 2006) but often with the goal of explaining the origins of certain prosodic and phonological characteristics of CDS as a by-product of utterance-length differences.…”
Section: Gap 1: Comparisons Between Cds and Ads In Morphosyntactic Le...mentioning
confidence: 69%
“…However, to ascertain what role features that distinguish CDS from ADS may play in language development it is necessary to examine their effects on learning gains, as we will discuss in Section 3. A deeper understanding of the function of CDS also benefits from comparing it to ADS sampled from a greater variety of contexts and situations (Weinstein & Baldwin, 2022), and to other forms of speech directed at different addressees like foreigner-directed speech (e.g., Piazza et al, 2022), pet-directed speech (e.g., Burnham et al, 2002) or elderspeak (e.g., Kemper & Harden, 1999).…”
Section: Comparing Morpho-syntax Vocabulary and Pragmaticsmentioning
confidence: 99%
“…play time, meal time, grooming and bed-time routines) differ markedly from the situational contexts in which adults tend to interact with each other. In most studies, ADS corpora tend to differ in context and content and therefore introduce a range of situational and contextual confounds into the comparison (Weinstein & Baldwin, 2022. Even if children and adults are placed in similar situations, speech to young children tends to focus on the here and now while adults often talk about topics displaced in space and time (Foushee et al, 2023).…”
Section: Comparing Morpho-syntax Vocabulary and Pragmaticsmentioning
confidence: 99%
See 2 more Smart Citations